2017
DOI: 10.16925/pe.v13i21.1710
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos de sueño, desempeño académico y comportamiento en niños de básica primaria

Abstract: ResumenIntroducción: una reducción del tiempo de sueño o la presencia de alteraciones en el mismo, trae repercusiones negativas en el funcionamiento de cualquier persona durante la vigilia. Objetivos: el presente estudio tuvo como propósito identificar la relación de los hábitos de sueño con el desempeño académico y el comportamiento en niños de básica primaria. Metodología: los participantes fueron 405 niños y niñas matriculados en instituciones educativas oficiales y privadas. Los padres de familia respondie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Sleep affects behavioral and emotional regulation in children (Gregory & Sadeh, 2012;Kamphuis et al, 2012;O'Brien et al, 2011;Vriend et al, 2013). Poor sleep hygiene, irregular sleep schedules, sleep deprivation, and sleep disorders are associated with a greater tendency to exhibit behavioral problems, lack of attention, increased propensity for aggression, and hyperactivity (Alfano et al, 2009;Dahl, 2006;Haynes et al, 2006;Kamphuis et al, 2012;Muñoz-Quintero & Bianchi, 2017;Peach & Gaultney, 2013). The behavioral problems that may arise due to poor sleep quality are associated with a higher prevalence of aggressive behaviors directed at other individuals, both in children and adolescents (Muñoz-Quintero & Biachi, 2017;O'Brien, 2009).…”
Section: Sleep and Bullying Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep affects behavioral and emotional regulation in children (Gregory & Sadeh, 2012;Kamphuis et al, 2012;O'Brien et al, 2011;Vriend et al, 2013). Poor sleep hygiene, irregular sleep schedules, sleep deprivation, and sleep disorders are associated with a greater tendency to exhibit behavioral problems, lack of attention, increased propensity for aggression, and hyperactivity (Alfano et al, 2009;Dahl, 2006;Haynes et al, 2006;Kamphuis et al, 2012;Muñoz-Quintero & Bianchi, 2017;Peach & Gaultney, 2013). The behavioral problems that may arise due to poor sleep quality are associated with a higher prevalence of aggressive behaviors directed at other individuals, both in children and adolescents (Muñoz-Quintero & Biachi, 2017;O'Brien, 2009).…”
Section: Sleep and Bullying Behaviormentioning
confidence: 99%
“…It is extremely important to become acquainted with children's sleep habits and sleep quality and learn the impact these factors can have on variables such as behavior. To do this, several studies investigated the relationship between sleep and neurobehavioral functioning (Blunden & Chervin, 2008;Ravid, Afek, Suraiya, Shahar, & Pillar, 2009) and found that sleep problems undeniably have an impact on children's daytime functioning, leading to more irritability, restlessness, symptoms of depression, aggressive behavior, and inattention (Muñoz-Quintero & Bianchi, 2017). Other studies have also demonstrated the existence of a relationship between poor sleep quality and aggressive behavior towards peers, antisocial behavior, hyperactivity, and attention deficit (Beebe, 2011;Biggs at al., 2011).…”
Section: Sleep and Bullying Behaviormentioning
confidence: 99%